Las inversiones y el resultado económico de la empresa Electro Oriente S.A. periodo 2016 - 2020 - Collantes Lozano, Angello (2022)
Electro Oriente S.A. is the company that generates, transmits, distributes and markets electricity in the regions of Loreto, San Martín, Amazonas and Cajamarca. The objective of the present investigation is to determine the relationship between the investments and the economic result of the company Electro Oriente SA, in the period 2016 - 2020. In line with this objective, the present Quantitative study is carried out, Correlational level and non-experimental design. The investigation concludes that there is no relationship between the investments and the economic result of the company in the period 2016 - 2020, a conclusion based on the result of the Correlation Coefficient that was r = -0.255773482; and the Coefficient of Determination R2 = 0.065420074; results that demonstrate the non-existence of statistical association and determination between the aforementioned variables. Likewise, the category of income that obtained most of the same as Sale of Services, with an amount of S/. 2,546,381,437.00 which is equivalent to 94.31% of the total. Expenditures were grouped under the Purchase of Goods concept, which amounted to the sum of S/. 1,605,286,649.00; figure that represents 66.21% and was constituted by the acquisition of inputs and supplies, fuels and lubricants. Investments show a variable behavior throughout the period, the highest figure being in 2019 with S/. 79,408,477.00; and the lowest in 2017 with S/. 4,940,577.00.